2012
DOI: 10.1002/ceat.201200259
|View full text |Cite
|
Sign up to set email alerts
|

Active and Stable Ni‐MgO Catalyst Coated on a Metal Monolith for Methane Steam Reforming under Low Steam‐to‐Carbon Ratios

Abstract: A structured reaction system in the form of an Ni‐MgO catalyst reduced to nanoscale particle size and coated on a metallic monolith proved to be an active and stable system for methane steam reforming under a steam‐to‐carbon ratio of 1.5 and a temperature of 700 °C. The catalyst‐coated monolith exhibited higher stability and much higher CH4 conversion than the same catalyst in a catalyst particle bed reaction system. The high activity is attributed to the properties of the metal monolith and to the small size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…It illustrates that the spacing of cylinders has no significant effect on the final state of reaction. The present work achieves a methane conversion of 95% (see Figure 7 ); it generally higher than improved performance of 91% and 93% conversion in previous experimental research [ 20 , 21 ] (inlet flow rate 0.75 and 2; temperature of feed 873 K and 943 K), partially due to higher operating temperature. As shown in Figure 8 , larger cylinder spacing results in higher conversion and the time to steady state is decreased (from 40 s to 20 s).…”
Section: Resultscontrasting
confidence: 59%
“…It illustrates that the spacing of cylinders has no significant effect on the final state of reaction. The present work achieves a methane conversion of 95% (see Figure 7 ); it generally higher than improved performance of 91% and 93% conversion in previous experimental research [ 20 , 21 ] (inlet flow rate 0.75 and 2; temperature of feed 873 K and 943 K), partially due to higher operating temperature. As shown in Figure 8 , larger cylinder spacing results in higher conversion and the time to steady state is decreased (from 40 s to 20 s).…”
Section: Resultscontrasting
confidence: 59%
“…Catalytic methane decomposition (CMD) to hydrogen and carbon is an interesting alternative to other conventional hydrogen production routes, such as steam reforming of methane [1], partial oxidation of methane [2], etc., since CO x emissions can be potentially avoided. Therefore, it is environmentally attractive with the increasing concern of the global warming problems associated with the over load emission of carbon dioxide into the earth.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst was prepared by soaking of the MgO support in aqueous solution of nickel nitrate and corresponding nitrates of the metals used as a promoter, followed by drying, calcination, and reduction. A study of O 2 chemisorption on the Ni/MgO catalyst indicated that the catalyst obtained from the impregnation solution of the lowest concentration has the smallest Ni crystallites; the Ni crytsllite size increases with the number of impregnation steps (Mehran et al 2011, de Miguel et al 2012. The high surface area of MgO is highly capable of reacting with H 2 O in order to produce Mg(OH) 2 during aqueous impregnation.…”
Section: Ni/mgo Heterogeneous Catalystmentioning
confidence: 97%
“…It is reported that Co/MgO catalyst can significantly raise the yield of single-walled CNTs with better quality. The incorporation of Mo might possibly decorate the edge of Co particles and thus increase the number of nanoparticles suitable for the growth of CNTs (Yang et al 2011, de Miguel et al 2012. Furthermore, the partial order of H 2 is not expressively different from zero and the activation energies were detected to be 150-163 kJ mol -1 and 96 kJ mol -1 for Mo-Co/MgO and Co/MgO catalysts, respectively, at 823-923 K. It has been proven that the growth of CNTs with catalyst-supported MgO does not depend on H 2 partial pressure (Shi and Zhang 2015).…”
Section: Mgo Support Catalyst In Cnt Synthesismentioning
confidence: 99%